Targeting vaginal dysbiosis: prospects for the application of live biotherapeutics products - Zhang, Qiongqiong; Zhao, Xiaoxiao; Chen, Zhangran; Chen, Rui; Lin, Xiong; Zhang, Lei; Li, Kangning; Wang, Min; Liu, Yanmin; Zhou, Huan; Liao, Qinping (Frontiers in Microbiology, 2026)
As a pivotal defense system within the female lower genital tract, the healthy vaginal microecosystem, dominated by Lactobacillus, safeguards against pathogenic microorganisms and maintains overall reproductive health through producing antimicrobial substances and sustaining an acidic environment. However, this intricate ecosystem is susceptible to a variety of adverse factors that trigger vaginal microbiota (VMB) dysbiosis, which further precipitate vaginal infections and gynecological disorders. Based on rigorous clinical evidence, this review systematically summarizes current mechanistic understanding of Lactobacillus-mediated VMB homeostasis. It evaluates the therapeutic potential of probiotics in both pharmaceutical and dietary supplement forms, and discusses the clinical necessity and existing challenges in developing live biotherapeutic products (LBPs) targeting the vaginal microecology. By integrating perspectives from both basic research and translational medicine, this work provides a theoretical foundation for developing targeted microbiota modulation strategies, thereby advancing precision medicine approaches for the management of vaginal dysbiosis.